2019
DOI: 10.1002/cam4.2505
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of ponatinib in patients with bevacizumab‐refractory glioblastoma

Abstract: Background Responses to bevacizumab in glioblastoma (GBM) are not durable. Plasma levels of basic fibroblast growth factor (bFGF) increase at the time of tumor progression. By targeting vascular endothelial growth factor receptor (VEGFR), platelet‐derived growth factor receptor, Src, and FGF receptor pathways, ponatinib may potentially help to overcome some of the putative mechanisms of adaptive resistance. Methods We performed a phase II trial of ponatinib in patients with bevacizumab‐refractory GBM and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Bevacizumab could develop drug resistance within months. The efficacy of multi-kinase inhibitor Ponatinib in GBM patients is very limited in Bevacizumab-refractory GBM (NCT02478164) [ 132 ]. Also, patients who progress on VEGF R-TKi with Bevacizumab only benefit modestly [ 133 ].…”
Section: Glioblastomamentioning
confidence: 99%
“…Bevacizumab could develop drug resistance within months. The efficacy of multi-kinase inhibitor Ponatinib in GBM patients is very limited in Bevacizumab-refractory GBM (NCT02478164) [ 132 ]. Also, patients who progress on VEGF R-TKi with Bevacizumab only benefit modestly [ 133 ].…”
Section: Glioblastomamentioning
confidence: 99%
“…VEGFR2 inhibitors induce FGF2 expression and accelerate the growth murine pancreatic neuroendocrine tumors (Casanovas et al, 2005). Clinical studies on glioblastoma furthers confirmed this observation (Batchelor et al, 2007;Lee et al, 2019).…”
Section: Fibroblast-growth Factorsmentioning
confidence: 77%
“…Due to ponatinib's unique multitargeted characteristics, further studies have demonstrated its ability in other human malignancies, such as GBM [ 47 ]. Eudocia Q Lee et al reported that they performed a phase II trial of ponatinib in patients with bevacizumab-refractory GBM and variants [ 48 ]. In addition, tyrosine-protein kinase that acts as a cell-surface receptor for VEGFA tyrosine-protein kinase inhibitors could reduce the VEGFA expression.…”
Section: Discussionmentioning
confidence: 99%